Joint association of multimorbidity and work ability with risk of long-term sickness absence: a prospective cohort study with register follow-up - Emil Sundstrup; Markus D Jakobsen; Ole Steen Mortensen; Lars L Andersen (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: The aim of this study was to determine the joint association of multimorbidity and work ability with the risk of long-term sickness absence (LTSA) in the general working population. METHODS: Cox regression analysis censoring for competing events (statutory retirement, early retirement, disability pension, immigration, or death) was performed to estimate the joint association of chronic diseases and work ability in relation to physical and mental demands of the job with the prospective risk for LTSA (defined as ≥6 consecutive weeks during 2-year follow-up) among 10 427 wage earners from the general working population (2010 Danish Work Environment Cohort Study). Control variables were age, gender, psychosocial work environment, smoking, leisure physical activity, body mass index, job group, and previous LTSA. RESULTS: Of the 10 427 respondents, 56.8% had experienced ≥1 chronic disease at baseline. The fully adjusted model showed an association between number of chronic diseases and risk of LTSA. This association was stronger among employees with poor work ability (either physical or mental). Compared to employees with no diseases and good physical work ability, the risk estimate for LTSA was 1.95 [95% confidence interval (95% CI) 1.50-2.52] for employees with ≥3 chronic diseases and good physical work ability, whereas it was 3.60 (95% CI 2.50-5.19) for those with ≥3 chronic diseases and poor physical work ability. Overall, the joint association of chronic disease and work ability with LTSA appears to be additive. CONCLUSIONS: Poor work ability combined with ≥1 chronic diseases is associated with high risk of long-term sickness absence in the general working population. Initiatives to improve or maintain work ability should be highly prioritized to secure sustainable employability among workers with ≥1 chronic diseases.